(untitled) (World Science, 2024)
Every day, a practitioner is faced with the problem of patient comorbidity. Bronchial asthma is a common problem, as is metabolic syndrome. Due to the increase in allergic diseases and lifestyle changes, patients may have a combination of metabolic syndrome and bronchial asthma. This combination has been shown to aggravate the course of asthma. Therefore, we wanted to confirm or refute this with our study. The study design included 94 patients with a diagnosis of asthma. A comparative analysis of the spirographic study data revealed that patients with asthma + MetS had statistically significant differences (p<0.05). The analysis of anthropometric data revealed that patients with the highest BMI and body weight had a significantly more severe course of asthma (p<0,05), which is consistent with the data of available world studies [24, 25], and a positive correlation was found between BMI, percentage of body fat and lower percentage of body fat in patients with severe asthma (ρ=0,89, ρ=0,90, ρ=0,87; r=0,88, r=0,91, r=0,90, respectively). The data obtained indicate the need for individual management of patients with comorbidities, including MetS and asthma, to prevent severe asthma, which is associated with inadequate asthma control and poor quality of life.